2021
DOI: 10.1177/20543581211060926
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcomes of Early Hospital Readmission in Canadian Kidney Transplant Recipients: A Population-Based Multi-Center Cohort Study

Abstract: Background: Early hospital readmissions (EHRs) occur commonly in kidney transplant recipients. Conflicting evidence exists regarding risk factors and outcomes of EHRs. Objective: To determine risk factors and outcomes associated with EHRs (ie, hospitalization within 30 days of discharge from transplant hospitalization) in kidney transplant recipients. Design: Population-based cohort study using linked, administrative health care databases. Setting: Ontario, Canada. Patients: We included 5437 kidney transplant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
(79 reference statements)
0
4
0
2
Order By: Relevance
“…Notably, EHR was associated with increased risk of acute rejection, graft loss, and death. Previous studies have shown that EHR is associated with higher mortality and graft loss in the first year of transplantation 3,4,8,16 . There is certainly an interaction between EHR and transplant era.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Notably, EHR was associated with increased risk of acute rejection, graft loss, and death. Previous studies have shown that EHR is associated with higher mortality and graft loss in the first year of transplantation 3,4,8,16 . There is certainly an interaction between EHR and transplant era.…”
Section: Discussionmentioning
confidence: 96%
“…There was an increase of EHR associated with diarrhea (1.4% vs. 9%, p = 0.013) in the New Era (Figure 3). There was no difference in time from index discharge to readmission (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) vs. 12 [IQR 6-20] days, p = 0.678) or in length of hospital stay during EHR (15 [IQR 8-25] vs. 13 [IQR 5-21] days, p = 0.157). The independent risk factors associated with EHR were older recipient, CMVnegative recipient, and longer DGF period (Table 2).…”
Section: Early Hospital Readmissionmentioning
confidence: 99%
“…Particularmente, a RHP foi associada ao aumento do risco de rejeição aguda, perda do enxerto e óbito. Estudos anteriores mostraram que a RHP está associada a maior mortalidade e perda do enxerto no primeiro ano de transplante 3,4,8,16 . Há certamente uma interação entre a RHP e a era do transplante.…”
Section: Discussionunclassified
“…Out of these, 52 full-text articles that aligned with the objective of the manuscript were reviewed. Ultimately, 17 studies were included in the final analysis, out of which twelve were cohort studies (10 retrospective, 1 prospective, and 1 ambispective) and one was a case-control study (5,(8)(9)(10)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Supplementary Figure 1 presents the PRISMA flowchart outlining the search process.…”
Section: Literature Search and Baseline Characteristicsmentioning
confidence: 99%